Արևմտահայերեն դարձվածային միավորների բառարանային զուգադրական քննություն - Արմինե Մկրտումյան (ՀՀ ԳԱԱ հրատ.)
Authօr compares some phraseologisms in several dictionaries as "Armenian phraseological dictionary" by A. Suqiasyan and S. Galstyan, "East and West Armenian orthoepic-defining dictionary" by R. Saqapetoyan, "Armenian phraseological defining dictionary" by P. Bediryan.
Keywords: Language and Literature